2018
DOI: 10.1111/jeu.12632
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Hidden Host Specificity of Chytrids Infecting Colonial Volvocacean Algae

Abstract: Chytrids are zoosporic fungi that play an important, but yet understudied, ecological role in aquatic ecosystems. Many chytrid species have been morphologically described as parasites on phytoplankton. However, the majority of them have rarely been isolated and lack DNA sequence data. In this study we isolated and cultivated three parasitic chytrids, infecting a common volvocacean host species, Yamagishiella unicocca. To identify the chytrids, we characterized morphology and life cycle, and analyzed phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 56 publications
(103 reference statements)
1
50
1
Order By: Relevance
“…This analysis revealed that the SV8 complex (and thus also all ASVs within this complex) groups within the order Lobulomycetales in the phylum Chytridiomycota (Figure 5). Specifically, the SV8 complex is nested within the recently defined Novel Clade SW-I (Van den Wyngaert et al, 2018) and is sister to several culture independent sequences obtained from the marine ecosystem (Hassett et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis revealed that the SV8 complex (and thus also all ASVs within this complex) groups within the order Lobulomycetales in the phylum Chytridiomycota (Figure 5). Specifically, the SV8 complex is nested within the recently defined Novel Clade SW-I (Van den Wyngaert et al, 2018) and is sister to several culture independent sequences obtained from the marine ecosystem (Hassett et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Although many of the ASVs observed here associated with Z. marina are still unidentified, we were able to phylogenetically place the SV8 complex in Novel Clade SW-I in the Lobulomycetales. Known members of Novel Clade SW-I are parasitic chytrids of freshwater algae and diatoms (Frenken et al, 2017; Rad-Menéndez et al, 2018; Van den Wyngaert et al, 2018). It is possible that the SV8 complex’s high relative abundance both on and in Z. marina leaves may indicate that it is directly infecting host plant tissues and suggests that seagrasses may provide a novel niche for marine chytrids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). As expected, zoospores of both chytrid species were rich in lipids, presenting a large lipid globule, a characteristic morphological feature of chytrids (Powell et al ., ; Van den Wyngaert et al ., ). Chytrids’ high lipid contents could explain the observed increase in total FA contents in Host+Sporangia fraction compared with the uninfected diatom host.…”
Section: Discussionmentioning
confidence: 97%